Circulating Tumor Cells in Esophageal Squamous Cell Carcinoma – Mini Review - Shi Y (Dove Medical Press, 2021)
Yujing Shi,1 Xiaolin Ge,2 Mengyang Ju,3 Yumeng Zhang,4 Xiaoke Di,2 Liang Liang1 1Jurong People’s Hospital, Zhenjiang, 212400, People’s Republic of China; 2Jiangsu Provincial People’s Hospital, Nanjing, 212000, People’s Republic of China; 3Department of Radiation Oncology, Osaka University Graduate School of Medicine, Suita, 5650871, Japan; 4Nanjing Medical University, Nanjing, 212000, People’s Republic of ChinaCorrespondence: Liang LiangJurong People’s Hospital, Huayang Town, Jurong City, People’s Republic of ChinaTel +86 511-8730 0705Email lianglvlv@yeah.netAbstract: Esophageal cancer has high incidence and mortality rates and a low five-year survival rate of < 15% owing to its strong capabilities of invasion, relapse and metastasis. The classic view holds that metastasis and diffusion is an advanced event during cancer progression, but recent studies show that distant diffusion of primary cancer cells may actually be an early event. Detection of circulating tumor cells (CTCs) in the circulation may indicate tumor spread, so CTCs are considered to be the key factor of metastatic cascade. In recent years, despite research progress on CTCs, there is a lack of systematic and important evidence to confirm the diagnostic, monitoring and prognostic values of CTCs in esophageal squamous cell carcinoma (ESCC). In this review, we clarify the relationship between CTC values and ESCC and provide more reliable evidence to improve the management and treatment of ESCC.Keywords: esophageal squamous cell carcinoma, circulating tumor cells, diagnostic, prognostic